Studies in diabetes - Stevens, Martin J.; Yorek, Mark A.; Obrosova, Irina (Oxidative Stress in Applied Basic Research and Clinical Practice, 2014)
Studies on Diabetes examines how increased oxidative and nitrosative stress - one of the leading causes of diabetes complications - pathologically affects multiple tissues in the body. The volume editors and chapter authors are leading investigators in the field of basic and clinical research in diabetes and vascular disease. Their contributions represent a wealth of knowledge on and research into how diabetes triggers metabolic abnormalities that lead to hyperactivation of cellular and mitochondrial pathways that ultimately result in oxidative and nitrosative stress that, left un-neutralized, results in tissue damage. Each chapter  provides the reader with invaluable insight to the complicated mechanisms responsible for diabetes complications and vascular disease. Potential treatments for diabetes complications from animal models to the patient will also be discussed. This is essential reading for researchers and clinicians in endocrinology, diabetes, vascular disease and oxidative stress.